If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 2 = -1(3x + 3) Reorder the terms: 2 + x = -1(3x + 3) Reorder the terms: 2 + x = -1(3 + 3x) 2 + x = (3 * -1 + 3x * -1) 2 + x = (-3 + -3x) Solving 2 + x = -3 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 2 + x + 3x = -3 + -3x + 3x Combine like terms: x + 3x = 4x 2 + 4x = -3 + -3x + 3x Combine like terms: -3x + 3x = 0 2 + 4x = -3 + 0 2 + 4x = -3 Add '-2' to each side of the equation. 2 + -2 + 4x = -3 + -2 Combine like terms: 2 + -2 = 0 0 + 4x = -3 + -2 4x = -3 + -2 Combine like terms: -3 + -2 = -5 4x = -5 Divide each side by '4'. x = -1.25 Simplifying x = -1.25
| 0=5-4x^3 | | 2x^4-22x^2+41=0 | | f(x)=5-4x^3 | | (2z)0= | | 5-4x^3=0 | | 17b+3=422 | | 6-y+z=a | | 7x+-6x=10 | | -5.7(2y+5)-2.7(4y-6)= | | 20-(-50)=x | | 450=(15)(-3)+x | | (b+3)+6= | | 26=2(4)+2(x+4) | | 3k+7=2K+9 | | 9x+2=6x+47 | | -400.00x+4000=2000 | | (1-.73)x=2897.10 | | (1+0.73)x=2897.10 | | 5c+3-4c=-26+14 | | 5x^2+5x-20=0 | | 3.00*x+5=50 | | p=a+5+c | | 2-3i/3+2i | | 14=(3)(3)+x | | p=220/0.04(2) | | 2x+3(x+5)=130 | | 5x-x-18-4x=-36 | | 75/8=11/4v+7/2v | | (8m+6)+(-5m-6)= | | 2x-3/2x=7/10 | | 16x-3(4x+7)=6x+(2x+21) | | 16x-3(4x+7)=6x(2x+21) |